Analisis penggunaan user status oleh planner pada maintenance order di PT. Pupuk Kaltim - Mahendra, Yusril Masa; Hertadi, Christopher Davito Prabandewa (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study analyzes the use of user status by planners on maintenance orders (MO) that experienced a backlog of more than one month in Plant 1A, 3, 4, and 7 of PT Pupuk Kaltim during 2024 using Fishbone Diagram and Pareto Chart methods. The Fishbone Diagram is used to identify the root causes of the backlog, which are grouped into six main categories: Man, Method, Material, Machine, Measurement, and Environment. The results of the Pareto Chart analysis show that the backlog is mainly caused by factors such as Waiting Material (WMAT), Waiting for Confirmation (WCON), and Waiting for Shutdown (WSHU). Based on these findings, this study provides strategic recommendations to improve the effectiveness of the planning and management of MOs through the optimization of user status usage by planners. These findings are expected to help PT Pupuk Kaltim reduce MO backlogs and improve plant maintenance efficiency.